Do host countries really benefit from inward foreign direct investment? - Byungchae Jin; Francisco García; Robert Salomon (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
The supposed benefits of IFDI to host countries are nuanced and not always positive. IFDI can crowd out local innovation, relegating local firms to less innovative, less profitable market niches. Whether IFDI provides long-term growth outcomes for host countries is therefore an open question.
Keywords: 330